Daya terima makanan biasa pada pasien rawat inap RSUD Provinsi Sulawesi Barat - Yudianti Yudianti; Riskayanti Riskayanti; Hapzah Hapzah; Najdah Najdah; Nurbaya Nurbaya (Poltekkes Kemenkes Aceh, 2024)
Background: There are still quite a number of hospitals that leave food that exceeds the minimum standard limit. One of the reasons for this is because the taste and appearance of the food served by the hospital does not meet the patient's acceptance.Objectives: This study aimed to assess the acceptability of regular food and food waste in inpatients at the West Sulawesi Provincial Regional Hospital.Methods: Data collection was carried out using observation, interviews, and recording leftover food that had been distributed to patients using the Comstoc method. The data collection period was carried out at the West Sulawesi Provincial Regional Hospital in June 2023. The total sample was 30 patients. Data analysis involves calculating the food acceptability score and displaying it descriptively.Results: The majority of patients, namely 83,3%, liked the taste of the food and 80% of patients really liked the appearance of the food served. Only 3% said they did not like the taste of food. Most patients produce their food at breakfast (63,3%), lunch (60%) and dinner (53,3).Conclusion: Most of the inpatients at West Sulawesi Provincial Regional Hospital like the taste and appearance of the regular food served. Lack of appetite is the main reason why patients waste food.